Model Matematics Salinitas Air di Muara Sungai untuk Pengairan Tambak Udang Windu - Andri Sewoko; Saiful Rochdyanto; Putu Sudira (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2003)
The salacca (Salacca zalacca cv. Pondoh) fruits were stored in various modified atmosphere conditions in the impermeable cuverles with the variation of oxygen concentration of 2, 4, 6 and 8%. carbon dioxide concentration of 1, 2. 3 and 4% and nitrogen concentration as the rest. The variation of temperature was 12, 20 and 24 C. Gases within each cuvette were replaced daily. The respiration rate of the fruit was mudded based on the enzyme kinetic theory. The result showed that the respiration model Mows the Michaelis-Menten enzyme kinetic, with CO2 as the uncompetitive inhibitor. The model was fit to predict the respiration rate of the fruit.